Using an on-site modular training approach to amplify prep service delivery in public health facilities in Kenya - Elizabeth M. Irungu; Moses Musau; Bernard Nyerere; Anabelle Dollah; Benn Kwach; Emmah Owidi; Elizabeth Wamoni; Josephine Odoyo; Nelly Mugo; Elizabeth Bukusi; Kenneth Mugwanya; Jared M. Baeten (PLOS Global Public Health, 2022)
Delivery of oral PrEP, a potent HIV prevention intervention, has begun within public health systems in many countries in Africa. Training as many health providers as possible expeditiously is necessary to efficiently and rapidly scale up PrEP delivery among at risk populations and thereby realize the greatest impact of PrEP. We designed and implemented an innovative on-site modular training approach delivered in five two-hour modules. The modules could be covered in two consecutive days or be broken across several days enabling flexibility to accommodate health provider work schedules. We assessed knowledge gain comparing pre-and post-training test scores and determined monthly PrEP uptake for six months following the training intervention. We also evaluated the cost of this training approach and conducted key informant interviews to explore acceptability among health providers. Between January 2019 and December 2020, 2111 health providers from 104 health facilities were trained on PrEP. Of 1821 (83%) providers who completed both pre- and post-tests, 505 (28%) were nurses, 333 (18%) were HIV counsellors, 276 (15%) were clinical officers and 255 (14%) were lay providers. The mean score prior to and after training was 58% and 82% respectively (p <0.001). On average, health facilities initiated an average of 2.7 (SD 4.7) people on PrEP each month after the training, a number that did not decline over six months post-training (p = 0.62). Assuming Ministry of Health costs, the costs per provider trained was $16.27. Health providers expressed satisfaction with this training approach because it enabled many providers within a facility receive training. On-site modular training is an effective approach for improving PrEP education for health workers in public health facilities, It is also acceptable and low-cost. This method of training can be scaled up to rapidly amplify the number of health workers able to offer PrEP services.